HARMONISASI HUKUM KONTRAK DAN DAMPAKNYA PADA HUKUM KONTRAK INDONESIA - Hutabarat, Samuel (Veritas et Justitia, 2016)
International commercial contracts are contracts closed by parties coming from different countries or made under “foreign” legal systems. Parties may have different understandings about how to read the contract and therefore it is of importance to include in the contract a provision on settlement of disputes containing choice of forum and/or choice of law. A different way to prevent conflicts and disputes stemming from the interpretation and implementation of international commercial contracts is by way of harmonization of national contract laws. Indonesia as an active member of the international (commercial) community should take the initiative to do so.  In other words, revision of the existing Indonesian contract law is much needed.  Keywords: contract, harmonize, international commercial contract